2012
DOI: 10.1371/journal.pone.0050976
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Novel Alzheimer’s Disease Risk Genes in Control and Alzheimer’s Disease Brains

Abstract: Late onset Alzheimer’s disease (LOAD) etiology is influenced by complex interactions between genetic and environmental risk factors. Large-scale genome wide association studies (GWAS) for LOAD have identified 10 novel risk genes: ABCA7, BIN1, CD2AP, CD33, CLU, CR1, EPHA1, MS4A6A, MS4A6E, and PICALM. We sought to measure the influence of GWAS single nucleotide polymorphisms (SNPs) and gene expression levels on clinical and pathological measures of AD in brain tissue from the parietal lobe of AD cases and age-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
230
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(246 citation statements)
references
References 55 publications
10
230
3
3
Order By: Relevance
“…ABCA7 is reported to be associated with phospholipid transport, similar to ABCA1 (40), and is linked to Alzheimer's disease (41,42). However, to date, no report has demonstrated the association of ABCA7 with antitumor drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…ABCA7 is reported to be associated with phospholipid transport, similar to ABCA1 (40), and is linked to Alzheimer's disease (41,42). However, to date, no report has demonstrated the association of ABCA7 with antitumor drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…CD33 function in the CNS, however, was not well studied until a series of genome-wide association studies identified CD33 variants that modified risk for developing AD [116][117][118]. It was later shown that CD33 expression levels correlate with cognitive decline in AD patients [119], and that the protective CD33 variant reduces CD33 expression [120]. Taken together, these data suggest that CD33 promotes AD pathogenesis.…”
Section: Siglecs/sialic Acidsmentioning
confidence: 99%
“…In addition, the effect of the 5XFAD transgene significantly altered the expression of genes known to be misregulated in AD, particularly Bin1, Cd33, Clu (Karch et al, 2012), Trem2 (Piccio et al, 2016), and C1qa (Hong et al, 2016), Figure 1F. However, the impact of causal FAD mutations on cognitive performance and risk gene expression varied widely depending on the specific background strain evaluated.…”
Section: Introductionmentioning
confidence: 99%